A review of curricular approaches and quality of life indicators in the united states for individuals displaying profound multiple disabilities - Jonna L. Bobzien (Social Welfare: Interdisciplinary Approach, 2011)
During the last two decades in the United States, there has been an increase in research studies on two salient areas of interests impacting individuals with profound multiple disabilities (PMD): providing access to appropriate educational curriculums and enhancing overall quality of life. Despite this interest, attempts to link positive quality of life indicators and appropriate educational curriculum for students with PMD have not been explored. The purpose of this literature review is to identify articles related to curriculum issues, as well as those addressing the importance of skill acquisition activities that lead to an improved quality of life. Implications for establishing a potential link between quality of life assessment practices and current educational practices in the United States are addressed.